Analisis Potensi Sumber Daya Perikanan dalam Pengembangan Ekonomi Maritim Kota Bima - Dina Anjelina (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
The identity of Indonesia as a maritime country can’t be separated from maritime history and geographical conditions with the vast sea area it has. The community's economic activities are also dependent on Indonesia's maritime potential, both in terms of natural resource management as well as marine industry and services. So, to optimize the pace of the national maritime economy, it’s very necessary to have consistent evaluation, strategy, and anticipation by the government in each region of Indonesia. Therefore, the author wants to analyze how big the government's role is in utilizing Indonesia's maritime potential, specifically fishery resources in Bima City, West Nusa Tenggara Province. The results of the analysis show that the Bima City government has basically made maximum efforts in developing its fishery resources, but has not yet achieved the strategic goals as written in the Bima City Marine and Fisheries Service Strategic Plan for 2018-2023.